Сhemiluminescent display - Jaguiro, P.; Stsiapanau, A.; Smirnov, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Investigation of organic liquid phase electroluminescence (traditionally, the
so-called “electro-chemiluminescence” or “electrogenerated chemiluminescence”) is of
special interest as a competitor for “liquid” and “solid” organic light emitted diodes
(OLEDs). From the electrochemical point of view, chemiluminescence is a selfregenerating
process providing high brightness light radiation due to recombination of
oppositely charged dye radicals. Chemiluminescent displays have a competitive set of
parameters: high light efficiency, low power consumption, low driving voltages, fast
response time, high spatial resolution, very high optical transmission and wide operation
temperature range. No polarizers or alignment layers are required. Samples of
chemiluminescent displays, including matrix microdisplays and micromechanically made
cells are available; its design and parameters are discussed in details. Theoretical and
experimental investigations of thin film DC chemiluminescence phenomena are carried
out. On the basis of obtained experimental results, the most important physical processes
have been investigated: charge injection into solution and charge transfer by
electrohydrodynamic flows. Further prospects of chemiluminescent display devices are
discussed.